2023
DOI: 10.1177/10776990231166941
|View full text |Cite
|
Sign up to set email alerts
|

The Versatility of Intersectionality in Journalism and Mass Communication Research

Abstract: Multiple and overlapping forms of oppression-what Black feminist legal scholar Kimberlè Crenshaw (1989) called intersectionality-is slowly emerging in the scholarship of journalism and mass communication (JMC). Intersectionality is particularly used to reveal the structural relations of power that denote hierarchies of privileges and punishment. Crenshaw (1989) argued that oppression is a complex phenomenon whose analysis must consider multiple characteristics of identity, including gender, race, ethnicity, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…From an intersectional perspective (Byerly et al, 2023), other important opposing patterns were found in relation to one positive and one negative representation. The positive news frame "Latinxs and Hispanics are employed in powerful positions" yielded lower perceptions, whereas the frame presented with a negative valence "Latinxs and Hispanics are employed in minimum-wage jobs" had higher perception rates across all variables: media exposure, ethnicity, race, income, age, sex, marital and work status.…”
Section: Enduring Stereotypical Constructsmentioning
confidence: 93%
“…From an intersectional perspective (Byerly et al, 2023), other important opposing patterns were found in relation to one positive and one negative representation. The positive news frame "Latinxs and Hispanics are employed in powerful positions" yielded lower perceptions, whereas the frame presented with a negative valence "Latinxs and Hispanics are employed in minimum-wage jobs" had higher perception rates across all variables: media exposure, ethnicity, race, income, age, sex, marital and work status.…”
Section: Enduring Stereotypical Constructsmentioning
confidence: 93%
“…Intersectionality, therefore, offers a framework for recognizing and tackling the specific obstacles encountered by people who belong to multiple marginalized groups (Randall and Curran, 2023). The notion of intersectionality has been influential traction in various fields, including education, and serves as an analytical approach for exploring the complexities of identity and power dynamics (Cole, 2009;Ferree, 2018;Byerly et al, 2023;Wright, 2023). While providing a comprehensive way of thinking (Thomas, 2020;Woods and Brink, 2021), it offers a deeper understanding of the ways in which structural discrimination operates in society (Waitoller and Artiles, 2013).…”
Section: Intersectionality Of Cultural and Linguistic Diversity And D...mentioning
confidence: 99%